Genetic polymorphism of Pit-1|HinfI gene in Grati-Ongole Grade cattle at Indonesian Beef Cattle Research Station - Hartati, H.; Anwar, S.; Soewandi, B.D.P. (Journal of the Indonesian Tropical Animal Agriculture, 2018)
The pituitary transcription factor (Pit-1) gene is one of the considered genes that responsible to growth in cattle. A specific Pit-1|HinfI gene polymorphism located within exon 6(g.1256G>A) has been shown to be associated with growth and milk traits in cattle. This study aimed to identify the Pit-1|Hinf1 gene polymorphism in Grati-Ongole Grade cattle (Grati-OG cattle). A total of 107 genomic DNA of Grati-OG cattle were used in this study. The detection of polymorphism was performed by PCR-RFLP method. Only AB and BB genotypes were succesfully identified with the frequency of 0.009 and 0.991, respectively. Whereas, the frequency of A and B alleles were 0.005 and 0.995, respectively. The observed genotype frequencies in this population do not deviated from HWE. The value of Ho, He and PIC were 0.009, 0.009 and 0.009, respectively.In conclusion, the Pit-1|HinfI gene polymorphism in Grati-OG cattle is monomorphic and hence it should not be used in further association studies.